Muhammad Djamil Djambek: Ulama Pembaharu Minangkabau - Novita Siswayanti (Jurnal Lektur Keagamaan, 2014)
Sheikh Muhammad Jamil Djambek is a scholar of Islamic reformer in Minangkabau . He plays and took part in da'wah and tablig , especially broadcast practice of Islamic values in life Minangkabau communities, which has a philosophy of  adat basandi syara’ syara’ basandi Kitabullah. Beside that Sheikh Muhammad Djambil Djambek commonly known as Inyiak Djambek , also an expert Falak Sciences . Having Science Falak, he set the direction of Qibla prayer and has constructed  schedule of Ramadan Imsakiah. This research seeks to examine the persona profiles, roles, and gait Inyiak Djambek in the development and renewal of Islam in Minangkabau . The study used qualitative methods with a historical approach in revealing all aspects of the character's life, ranging from social background, education, role in propaganda and education activities  patterns of thought and religious works, books and figures influencing institutional heritage,, influence his thinking for the community, and so on.Keywords: Inyiak Djambek , Islamic reformer, Minangkabau